LTE backhaul planning and optimization - Metsala, Esa; Salmelin, Juha (Wiley, 2016)
The aim of this book is to enable network planners to realize and maintain cost efficient LTE backhaul networks, which meet the necessary performance requirements, the reader shall obtain all relevant information to achieve good backhaul results in their own network environment.